2017
DOI: 10.21475/ajcs.17.11.02.p5853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pre-harvest foliar calcium applications on ‘Fuji’ apple fruit quality during cold storage

Abstract: In this study, calcium chloride (CaCl 2 ) and two organic calcium compounds including Calcicat® and Folical® and water (as control) were applied at four different spray programs (All-season, Early, Mid and Late season spray) at the Abhar region in Iran during 2012 and compared. 6-year-old 'Standard Fuji' trees grafted on 'MM106' rootstock were used in this study. All spray programs involved 6 biweekly sprays. Fruits harvested at commercial maturity stage and stored at commercial cold storage at 0 º C and RH 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Optimal supply of apple fruits with this element is associated with better fruit firmness, higher content of soluble solids and total acids, better fruit coloration (Kadir 2005) and reduced occurrence of physiological diseases during storage (Fallahi et al 2010) without detrimental effect on consumer acceptance (Lester, Gursak 1999). CaCl 2 and calcium nitrate (Ca(NO 3 ) 2 ) are common calcium fertilizers used for spraying of apple (Ghorbani et al 2017). Experimental results https://doi.org/10.17221/127/2022-HORTSCI to 40 mm-T stage fruit (BBCH 74) and was repeated four times at every 20 days until one month before fruits were ripe for picking.…”
Section: Materials and Metodsmentioning
confidence: 99%
“…Optimal supply of apple fruits with this element is associated with better fruit firmness, higher content of soluble solids and total acids, better fruit coloration (Kadir 2005) and reduced occurrence of physiological diseases during storage (Fallahi et al 2010) without detrimental effect on consumer acceptance (Lester, Gursak 1999). CaCl 2 and calcium nitrate (Ca(NO 3 ) 2 ) are common calcium fertilizers used for spraying of apple (Ghorbani et al 2017). Experimental results https://doi.org/10.17221/127/2022-HORTSCI to 40 mm-T stage fruit (BBCH 74) and was repeated four times at every 20 days until one month before fruits were ripe for picking.…”
Section: Materials and Metodsmentioning
confidence: 99%
“…Li (2020) found that preharvest calcium treatment (1% and 2%) increased the activity of superoxide dismutase, catalase, and ascorbic acid peroxidase during late storage, thus delaying fruit ripening and enhancing the disease resistance of mango fruit [ 13 ]. Ghorbani (2021) found that spraying calcium during the growing period resulted in a significant increase in calcium concentration in apples and also significantly improved storage tolerance during the postharvest period [ 14 ]. In "Liberty" Blueberries, Lobos (2021) found a high positive correlation between fruit hardness and fruit calcium concentration [ 15 ].…”
Section: Introductionmentioning
confidence: 99%